Research progress in membrane fusion-based hybrid exosomes for drug delivery systems - Liu, Anqi; Yang, Gang; Liu, Yuehua; Liu, Tingjiao (Frontiers in Bioengineering and Biotechnology, 2022)
Liposomes are the earliest and most widely used nanoparticles for targeted drug delivery. Exosomes are nanosized membrane-bound particles and important mediators of intercellular communication. Combining liposomes and exosomes using various membrane fusion methods give rise to a novel potential drug delivery system called membrane fusion-based hybrid exosomes (MFHE). These novel MFHEs not only exhibit potential advantageous features, such as high drug loading rate and targeted cellular uptake via surface modification, but are also endowed with high biocompatibility and low immunogenicity. Here, we provide an overview of MFHEs’ various preparation methods, characterization strategies, and their applications for disease treatment and scientific research.